KOMUNIKASI KEBIJAKAN DALAM IMPLEMENTASI SISTEM APLIKASI KEUANGAN TINGKAT INSTANSI (SAKTI) DI KANTOR PELAYANAN PERBENDAHARAAN NEGARA KABUPATEN KLATEN - Alice Meizahra; Retna Hanani; Kismartini Kismartini (Journal of Public Policy and Management Review, 2023)
The implementation of the SAKTI (Institution Level Financial Application System) improve financial quality has not been fully optimized at KPPN Klaten. This research will examine how policy communication in the implementation of SAKTI at KPPN Klaten, and the driving factors and inhibiting factors that influence policy communication SAKTI at KPPN Klaten. The research method uses qualitative methods. The results of the study show that the transmission has been carried out by KPPN Klaten as the leading sector for the implementation of SAKTI in Klaten and Boyolali Regencies. The clarity of information transmission is not optimal due to the limited face-to-face meetings and the complexity of the modules at SAKTI. Consistency is not optimal because there is a change in information, but this is resolved by KPPN Klaten by continuing communication. The driving factors for SAKTI implementation communication are the credibility of the communicator, the existence of a legal basis for SAKTI implementation, as well as various communication channels. The inhibiting factors for SAKTI implementation communication are the limited number of SAKTI trainers and the implementation budget for SAKTI implementation support activities, the distance between the satker offices and KPPN Klaten, the quality of the work units, complex modules, and changes in SAKTI application information. The suggestion from this research is to increase the number of SAKTI trainers, and create a publication and information division so that communication channels about SAKTI can be maximized.